2016
DOI: 10.21873/anticanres.11002
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of PRKX, WNT3 and WNT16 in Human Nodular Basal Cell Carcinoma

Abstract: PRKX, WNT3 and WNT16 genes, belonging to the WNT signaling pathway, are involved in the tumorigenic process of nodular BCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…In addition to hair‐loss disorders, the SHG and bulge are of particular clinical relevance because they may give rise to at least some basal cell carcinoma (BCC) in human skin, and dysregulated Wnt signalling has also been implicated in BCC pathobiology . Clinically, this renders a systematic examination of Wnt signalling in these key epithelial progenitor cell compartments of human HFs important also from an oncological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hair‐loss disorders, the SHG and bulge are of particular clinical relevance because they may give rise to at least some basal cell carcinoma (BCC) in human skin, and dysregulated Wnt signalling has also been implicated in BCC pathobiology . Clinically, this renders a systematic examination of Wnt signalling in these key epithelial progenitor cell compartments of human HFs important also from an oncological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Among various Wnts associated with the canonical Wnt/-catenin signaling pathway, Wnt3 was previously reported being frequently up-regulated in human cancers [8, 32, 33]. However, recent researches demonstrated that Wnt3 was down-regulated in some types of cancers and related to worse prognosis [34, 35]. With regards to HCC, Wnt3 expression was reported to be upregulated in human HCC compared to the adjacent peritumoral tissue [13].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt3 overexpression has been commonly identified in aggressive tumors. Carmo et al pointed out that BCC is not an aggressive tumor, therefore there may be different gene expression profiles in such tumors [ 70 ].…”
Section: Crosstalk Between Hh Signaling Pathway and Other Signalinmentioning
confidence: 99%